Ferromagnetic resonance of magnetite films and iron nanowires - McGuigan, Louise (Trinity College (Dublin, Ireland). School of Physics, 2010)
Ferromagnetic resonance (FMR) measurements were carried out at 9.6 GHz on thin magnetite films and iron nanowire arrays, produced by molecular beam epitaxy (MBE). The aims of the studies were to examine how the magnetic anisotropy is affected by film thickness, the deposition substrate material, post-deposition annealing, and deposition on a stepped substrate. For films deposited on MgO, we found that the cubic anisotropy field, H4||, decreased with an increase in film thickness. This decrease was accompanied by an increase in the mean FMR peak-to-peak linewidth, which indicates a decrease in the film quality. H4|| was seen to increase after annealing for just 4 minutes in air at 250°C, with this change being accompanied by a significant decrease in the linewidth. We propose that the annealing treatment is altering the defects within the films, and increasing the magnetic ordering. A further anneal of 156 minutes did not affect the observed H4||, and the linewidth was seen to decrease only a little further. For all magnetite films deposited on MgAl2O4, we found the easy axis of magnetisation lie along [010] type directions as opposed to the expected [110] type directions. The cause of this unexpected result is not immediately apparent. Again, we propose that the film with higher cubic anisotropy is of better quality, as is shown by the quality of the FMR signal observed. H4|| again increased after annealing - however, in this case, almost no change is observed after 5 minutes annealing in air at 250°C, whereas a large increase in H4|| is observed after 160 minutes annealing. Similarly, the greatest change in linewidth is observed after 160 minutes of annealing.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin